1996
DOI: 10.1007/bf01887115
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence behavior of tryptophan residues of bovine and human serum albumins in ionic surfactant solutions: A comparative study of the two and one tryptophan(s) of bovine and human albumins

Abstract: The fluorescence behavior of two tryptophans (Trp-134, Trp-213) in bovine serum albumin (BSA) and a single tryptophan (Trp-214) in human serum albumin (HSA) was examined. The maximum emission wavelength (lambda max) was 340.0 nm for both proteins. In a solution of sodium dodecyl sulfate (SDS), the lambda max of BSA abruptly shifted to 332 nm at 1 mM SDS and then reversed to 334 nm at 3 mM SDS. The lambda max of HSA gradually shifted to 330 nm below 3 mM SDS, although it returned to 338 nm at 10 mM SDS. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
124
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(130 citation statements)
references
References 44 publications
(56 reference statements)
5
124
0
Order By: Relevance
“…22 Research has shown a significant difference between the functions of HSA and BSA. 23 The high homology and low cost of BSA makes it an appropriate research proxy for HSA. Therefore, BSA is widely used as a surfactant to control the synthesis of transition-metal ion-based NPs, a process similar to the biomineralization observed in nature.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Research has shown a significant difference between the functions of HSA and BSA. 23 The high homology and low cost of BSA makes it an appropriate research proxy for HSA. Therefore, BSA is widely used as a surfactant to control the synthesis of transition-metal ion-based NPs, a process similar to the biomineralization observed in nature.…”
Section: +mentioning
confidence: 99%
“…In this process, the transition-metal ions would play a similar role as inorganic NPs. 23 In a recent proof-of-concept experiment, gallic acid (GA)-Fe(III) coordination polymer NPs were explored as theranostic agents, given their strong absorbance in the NIR region and good MRI properties. 31,32 Here, GA-Fe was used to investigate the role of BSA in tuning the synthesis of coordination polymer NPs.…”
Section: +mentioning
confidence: 99%
“…13 On the other hand, the intrinsic fluorescence of the tryptophan (Trp) and tyrosine (Tyr) residues in albumin have also been used as probes in binding analyses. [14][15][16] HSA has only one Trp residue in the sub-domain IIA region, which has been considered to be the major drug-binding site of HSA. 17,18 Therefore, the fluorescence of the Trp in HSA (Trp-HSA) is a useful probe for the binding to this site.…”
Section: Introductionmentioning
confidence: 99%
“…Except for this, the amino acid compositions of the two proteins are nearly the same. HSA has one tryptophan group at the 214 position, while BSA has two tryptophan groups at 134 and 212 position (Moriyama et al, 1996;Mishra et al, 2005). Primarily, three domains and six principal binding sites have been identified for several important biomolecules.…”
Section: Introductionmentioning
confidence: 99%